Histone deacetylase-6 modulates Tau function in Alzheimer's disease - Qureshi, Tazeen; Chinnathambi, Subashchandrabose (Biochimica Et Biophysica Acta-Molecular Cell Research, 2022)
Alzheimer's disease (AD), one of the major tauopathies, is multifactorial with a massive demand for disease modifying treatments rather than symptom management. An AD-affected neuron shows Tau depositions generated due to overload on the proteostasis machinery of the cell and/or abnormal post-translational modifications on Tau protein. Loss of memory or dementia is the most significant concern in AD, occurring due to the loss of neurons and the connections between them. In a healthy brain, neurons interact with the environment and each other through extensions and migratory structures. It can thus be safe to assume that Tau depositions affect these growth structures in neurons. A Histone Deacetylase, HDAC6, has shown elevated levels in AD while also demonstrating direct interaction with the Tau protein. HDAC6 interacts with multiple proteins in the cell and is possibly involved in various signalling pathways. Its deacetylase activity has been a point of controversy in AD; however other functional domains remain unexplored. This review highlights the beneficial potential of HDAC6 in AD in mediating both Tau proteostasis and cytoskeletal rewiring for the neuritic extensions through its Ubiquitin Binding domain (HDAC6 ZnF UBP).
Keywords: Actin; Cytoskeleton; HDAC6; Microtubules; Proteostasis; Tau; ZnF UBP domain

Macrocyclic peptides derived from AcPHF6*and AcPHF6 to selectively modulate the Tau aggregation - Dangi, Abha; Qureshi, Tazeen; Chinnathambi, Subashchandrabose; Marelli, Udaya Kiran (Bioorganic Chemistry, 2024)
Ten macrocyclic peptides, each comprising 14 amino acids, were designed and synthesized based on the Tau aggregation model hexapeptides AcPHF6* and AcPHF6. The design took into account the aggregation tendencies of each residue in AcPHF6* and AcPHF6, their aggregation models, while employing peptide-based structural design principles including N-methylation to promote turns and to block hydrogen bond propagation and elongation of the aggregation chain. NMR analysis supported that all these peptides adopted an antiparallel beta-sheet conformation. Self-aggregation studies characterized the aggregation properties of these peptides, identifying two peptides with the highest (P3) and lowest (P8) aggregation tendencies. In cross-aggregation studies with the parent peptides AcPHF6* and AcPHF6, P3 and P8 were found to promote and reduce aggregation, respectively. Furthermore, P3 and P8 demonstrated an enhancement and diminution effect on the aggregation of K18wt, indicating their capacity to modulate aggregation even at the macromolecular level. Thus, the two simple peptides, P3 and P8 selectively exhibit pro- or anti-aggregation effects on PHF peptides and Tau. This study, has thus developed structurally well-defined non-complex peptides, derived from AcPHF6* and AcPHF6, to modulate Tau aggregation as desired, offering applications in Tau model studies and the development of Tau aggregation inhibitors or promoters.
Keywords: Cyclic peptides; Peptide -based drug design (PBDD); Peptide conformation; PHF peptides; Tau Aggregation